Breaking survival barriers in breast cancer- A case of CNS metastasis (Indian Journal of Case Reports, 2019)
One in every eight women worldwide will be diagnosed to be suffering with breast cancer in their lifetime. It is vital not only to diagnose the disease early but also to refer it to a tertiary care center for the most appropriate or standard anti-cancer treatment without delay. The outcomes of such therapy can be a game changer for the patient. Screening mammography is only having a small reduction in mortality of breast cancer. Here, we present a clinical report of one patient who had Her2 Neu positive disease with early central nervous system (CNS) metastasis and responded extremely well to anti her2 Neu therapy with chemotherapy and has survived over six years now on treatment.